Profile of Childhood Non-Hodgkin Lymphomas at a Tertiary Care Hospital - Gunge, Ratnaprabha Anil; Kalgutakar, Alka D (Indian Journal of Medical and Paediatric Oncology, 2019)
Context: Lymphoma was the second most common malignancy accounted for 22% of pediatric cases, of which 34 (68%) were non-Hodgkin’s lymphoma (NHL). Aims: To find the incidence, clinical presentations, laboratory findings, proportion of extranodal involvement, and to study histological subtypes (REAL/WHO classification) of NHL, compare them with reported case series in the world literature. Settings and Design: Gross specimens and biopsies of pediatric NHL were retrieved from the Department of Surgical Pathology from the year 2004 to 2013 at a tertiary care hospital. Patients and Methods: Gross and microscopy of incisional biopsies and surgically resected specimens of pediatric cases were studied using hematoxylin and eosin stain and wherever needed special stain and immunohistochemistry were used. Results: The incidence of NHL was higher in more than 10 years of age group with male predominance. Burkitt’s lymphoma (BL) (41.2%) was the most common subtype followed by T-lymphoblastic lymphoma (T-LL) (29.4%). Predominantly extranodal presentation was seen, BL presented as ileocecal masses (five cases) and orbital swelling (three cases). T-LL presented as a mediastinal masses (six cases). Rare cases of precursor B-LL involving orbital mass and plasmablastic lymphoma involving paranasal sinuses were studied. Among bone marrows studied a case of T-LL developed pancytopenia, during chemotherapy showed giant pronormoblast (Parvovirus infection). HIV association was seen in five cases of NHL. Postchemotherapy disease-free survival was very low and many patients died during chemotherapy. Conclusion: Although the incidence of HL is higher in children, in the present study, NHL with extranodal presentation (58%) involving rare sites with poor prognosis is higher, 15% of all cases showed HIV seropositivity.
Keywords: Burkitt’s lymphoma; Non-Hodgkin lymphoma; Plasmablastic lymphoma; Precurser B- lymphoblastic lymphoma; T - lymphoblastic lymphoma